Hospitalization and death after recovery from acute COVID‐19 among renal transplant recipients. Issue 4 (10th January 2022) - Basic‐Jukic, Nikolina; Racki, Sanjin; Tolj, Ivana; Aleckovic, Mirna; Babovic, Batric; Juric, Ivana; Furic‐Cunko, Vesna; Katalinic, Lea; Mihaljevic, Dubravka; Vujic, Sofija; Mesic, Enisa; Jelakovic, Bojan; et al.
Abstract: Introduction: Data on post‐COVID‐19 in renal transplant recipients (RTR) is scarce. We investigated the rate of hospitalizations, reasons for hospital admission, and mortality rate among RTR who survived acute COVID‐19. Methods: A multi‐center retrospective observational cohort study measured hospital admission and death to 180 days after acute SARS‐CoV‐2 infection in 308 adult patients. Results: The median age was 57 years, 64.9% were male. All patients had at least one comorbidity, and 26.3% had diabetes. Data on post‐COVID‐19 course was available for 267 patients, and 49 of them (15.9%) required hospital treatment after recovery from the acute infection. The most common indications included pneumonia (24.5%) and renal allograft dysfunction (22.4%), 7 (14.3%) had sepsis and 5 (10.2%) had thrombotic events. A median duration of the hospital stay was 12 days. Six patients (2.2%) died due to multiorgan failure, respiratory insufficiency or urosepsis. The strongest predictor for hospitalization after acute COVID‐19 was hospitalization for acute SARS‐CoV‐2 infection, while better allograft function decreased the probability of hospitalization. Conclusion: Delayed consequences of acute COVID‐19 are highly prevalent and the health care systems should be prepared to respond to the needs of RTR suffering from post‐COVID‐19 complications.